Computer Software and Services to Arabic Language - Abdulraheem Asalejo, Abdulrafiu (Kashere Journal of Humanities, Management and Social Sciences, 2022)
The contribution of information and communication technology in making life easy for humanity cannot be overemphasized. The computer is certainly the cutting edge of the human technology, as it assists globally in achieving some difficult tasks like knowledge and information. This is the learning of computer has become a necessity that man should endeavor to get with every possible strategy. The Government of Nigeria has spent a considerable amount on computer education in Nigerian schools from elementary school to university level since 1987. But most Arabic language students in Nigeria and their teachers hardly understand this global development, as they continue their training as if they are not in the same atmosphere and environment with their counterparts in other disciplines. This research considered these challenges and presented some useful programs for Arabic studies, with their benefits and uses, particularly, in the areas of teaching, learning and researching.